Verb and noun word retrieval in bilingual aphasia: a case study of language- and modality-specific levels of breakdown - Kambanaros, Maria (My University, 2016)
This study reports on the pattern of performance on spoken and written naming, spelling to dictation, and oral reading of single verbs and nouns in a bilingual speaker with aphasia in two first languages that differ in morphological complexity, orthographic transparency, and script: Greek (L1a) and English (L1b). The results reveal no verb/noun grammatical class differences in spoken naming or reading aloud in either language. For the written modality, only one task (spelling dictated words) in only one language (Greek) showed a grammatical class difference with verbs significantly easier to spell than nouns. Written picture naming revealed no verb/noun grammatical class difference in either language, suggesting an impairment specific to spelling processes for nouns in Greek. In general, the findings reveal no overall difference in processing verbs and nouns across languages, tasks, and modalities.
Keywords: Bi-/multilingualism; Grammatical word class processing; Reading out loud; Spelling to dictation; Spoken and written picture naming